Acute Sheehan's syndrome presenting as central diabetes insipidus. (6th November 2012) - Robalo, Raquel; Pedroso, Célia; Agapito, Ana; Borges, Augusta
Abstract : Sheehan's syndrome occurs as a result of ischaemic pituitary necrosis due to severe postpartum haemorrhage. Improvements in obstetrical care have significantly reduced its incidence in developed countries, but postpartum pituitary infarction remains a common cause of hypopituitarism in developing countries. We report a case of severe postpartum haemorrhage followed by headache, central diabetes insipidus and failure to lactate, which prompted us to investigate and identify both anterior and posterior pituitary deficiency compatible with Sheehan's syndrome. A timely diagnosis allowed us to implement an adequate treatment and follow-up plan, which are known to improve clinical status and patient outcome.